Increment Production of some Active Compounds in Datura stramonium L. Callus Stimulated by Manganese Oxide Nanoparticles - Jassim, Emad Hamdi; Abed, Ashwaq S. (Iraqi Journal of Science, 2025)
Alkaloids were deliberated  in the leaves and callus of Datura stramonium L. to  evaluate different nano-stimulated treatments to augment  bioactive substances in the callus. Datura callus cultures were established on Murashige and Skoog (MS) medium supplemented with naphthaleneacetic acid (NAA) at 1 mg/L and benzyl adenine (BA) at 0.5 mg/L. The results recorded a maximum callus fresh and dry weight (547.56 and 50.76 mg, respectively). The HPLC assay detected three alkaloids from the callus and leaves of D. stramonium . The analysis displayed that the callus cultures that developed on the cultural medium were lacking manganese oxide nanoparticles (MnO2-NPs), recorded valuable content of hyoscyamine, hyoscine, and atropine (10.9, 13.3, and 8.6 µg/g, respectively). These values indicate increases of 1.8, 2.1, and 1.6-fold, respectively, over the levels recorded from Datura leaves, which were 6.1, 6.4, and 5.4 µg/g, respectively. Moreover, several doses of MnO2-NPs (0, 50, 100, 150, 200, 250, and 300 mg/L) were added to the cultural medium to evaluate their effect on callus growth, alkaloid content, and antioxidant activity in the developed callus on these treatments. It was found that the dose of 250 mg/L recorded 31.9, 40.1, and 27.9 µg/g of hyoscyamine, hyoscine, and atropine, respectively. These levels showed a 2.9, 3.0, and 3.2-fold elevation compared to the control treatment. Regarding the radical scavenging assay (DPPH), the callus culture treated with a dose of 300 mg/L had a higher level of inhibition (55.6 %) than other treatments. Overall it found that the used of the nano catalyst had a positive effect in increasing the alkaloid compounds under study.